1998
DOI: 10.1002/j.2161-007x.1998.tb00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Spiritual Dimension Into Traditional Counselor Education Programs

Abstract: The author explores the issues involved in integrating the spiritual dimension into traditional counselor education by creating a joint community and addictions counseling master's program based on a hybrid of the wqunded healer and wellness models. Such a hybrid encompasses both the skills and knowledge approaches to counselor education advocated by the Council for Accreditation of Counseling and Related Educational Programs and the spirituality of Alcoholics Anonymous's 12 steps. After a theoretical discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A number of authors of theoretical articles (Bishop, Avila-Juarbe, & Thumme, 2003;Burke et al, 1999;Hall, Dixon, & Mauzey, 2004;Matthews, 1998;Myers & Williard, 2003) have argued for greater inclusion of spiritually oriented competencies in the field of counseling. Many of these scholars have pointed to the key role that the Council for the Accreditation of Counseling and Related Educational Programs (CACREP; 2001) plays in advocating for preparing counselors in spiritual diversity issues.…”
Section: Counselor Educationmentioning
confidence: 99%
“…A number of authors of theoretical articles (Bishop, Avila-Juarbe, & Thumme, 2003;Burke et al, 1999;Hall, Dixon, & Mauzey, 2004;Matthews, 1998;Myers & Williard, 2003) have argued for greater inclusion of spiritually oriented competencies in the field of counseling. Many of these scholars have pointed to the key role that the Council for the Accreditation of Counseling and Related Educational Programs (CACREP; 2001) plays in advocating for preparing counselors in spiritual diversity issues.…”
Section: Counselor Educationmentioning
confidence: 99%
“…In 1989, the American Association of Counseling and Development's Governing Council passed a resolution endorsing the wellness paradigm as the philosophical foundation for the counseling profession (Myers, 1991). The key role that spirituality plays in wellness has since been explicated by Myers (199 1, 1992; see also Chandler et al, 1992;Matthews, 1998;and Witmer & Sweeney, 1992). Matthews (in press) proposed that the wellness paradigm is a key to integrating addictions counseling into traditional counselor education programs and described an experimental program that attempted to foster not only the academic but also the psychological and spiritual development of students.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the client resonates to an authentic person, a guide who is willing to use his or her whole self in relation to the client's process of healing (Small, 1987). Matthews (1998) and Matthews and Hollingsworth (1999) have stressed the importance of substance abuse counselors' spiritual well-being and described an experimental master's program in community and addictions counseling that seeks to include the spiritual realm as well as the academic. However, no specific studies have been found that looked empirically at the spiritual well-being of substance abuse counselors and the impact of their well-being on clients in their clinical care.…”
mentioning
confidence: 99%
“…In spite of generations of oppression and persecution, the tribal traditions and ceremonies of many Native nations have survived and flourished. In addition, the need for incorporating spirituality into both counseling and the conceptualization of client issues is more than apparent (Curtis & Davis, 1999;Holden, 2000;Matthews, 1998). Although some controversy exists regarding the appropriateness of incorporating Native spiritual traditions into counseling with both Native and non-Native clients, it is our opinion that the essence of certain practices can be used in a way to benefit any client without disrespecting the Native tradition from which it originates.…”
mentioning
confidence: 93%